Author Correction: Live Intracellular Biorthogonal Imaging by Surface Enhanced Raman Spectroscopy using Alkyne-Silver Nanoparticles Clusters. Issue 1 (December 2018) - Ardini, Matteo; Huang, Jian-An; Sánchez, Carlos; Mousavi, Mansoureh; Caprettini, Valeria; Maccaferri, Nicolò; Melle, Giovanni; Bruno, Giulia; Pasquale, Lea; Garoli, Denis; Angelis, Francesco
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.